Capacity to consent to research participation in adults with metastatic cancer: comparisons of brain metastasis, non-CNS metastasis, and healthy controls. Issue 4 (9th March 2020) - Mulhauser, Kyler; Marotta, Dario A; Gerstenecker, Adam; Wilhelm, Gabrielle; Myers, Terina; Gammon, Meredith; Vance, David E; Nabors, Burt; Fiveash, John; Triebel, Kristen
Abstract: Background: To evaluate the ability of individuals with metastatic cancer to provide informed consent to research participation, we used a structured vignette-based interview to measure 4 consenting standards across 3 participant groups. Methods: Participants included 61 individuals diagnosed with brain metastasis, 41 individuals diagnosed with non-CNS metastasis, and 17 cognitively intact healthy controls. All groups were evaluated using the Capacity to Consent to Research Instrument (CCRI), a performance-based measure of research consent capacity. The ability to provide informed consent to participate in research was evaluated across 4 consent standards: expressing choice, appreciation, reasoning, and understanding . Capacity performance ratings (intact, mild/moderate impairment, severe impairment) were identified based on control group performance. Results: Results revealed that the brain metastasis group performed significantly lower than healthy controls on the consent standard of understanding, while both metastatic cancer groups performed below controls on the consent standard of reasoning . Both metastatic cancer groups performed similar to controls on the standards of appreciation and expressing choice . Approximately 60% of the brain metastasis group, 54% of the non-CNS metastasis group, and 18% of healthy controls showed impaired research consent capacity. Conclusions: Our findings, using a performance-based assessment, are consistent with other research indicating that the research consent process may be overly cumbersome and confusing. This, in turn, may lead to research consent impairment not only in patient groups but also in some healthy adults with intact cognitive ability.